KEWAJIBAN PENGGUNAAN BAHASA INDONESIA TERHADAP TENAGA KERJA ASING YANG BEKERJA DI WILAYAH NEGARA KESATUAN REPUBLIK INDONESIA - Muhammad Japri; Mohammad Doni Saputra Wijaya (LPPM STIH Awang Long, 2023)
The ASEAN Economic Community (AEC) was formed to realize ASEAN economic integration, namely achieving a safe ASEAN region with a higher and more integrated level of development dynamics, alleviating ASEAN communities from poverty, and economic growth to achieve equitable and sustainable prosperity. MEA opens up opportunities for the entry of foreign workers (TKA) into Indonesia so that competition in the employment sector becomes increasingly tight. The obligation to speak Indonesian was regulated through Minister of Manpower and Transmigration Regulation No. 12/2013 and previously through Minister of Manpower and Transmigration Decree No. KEP-20/MEN/III/2004. This state language is mandatory because there is a need to transfer knowledge and technology (science and technology) from the presence of foreign workers. This obligation began to be removed in the procedures for using foreign workers with the issuance of Minister of Manpower Regulation No. 16/2015. In this paper the author uses a normative juridical approach, because of his approach this model of legal research is called normative legal research. By using Primary Legal material in the form of Presidential Regulation Number 20 of 2018 (Article 26), which requires that employers, not foreign workers, learn Indonesian as a requirement for work competency.